Effects of Heavy Metals on the Performance and Mechanism of Anaerobic Ammonium Oxidation for Treating Wastewater - Ren, Qiang; Gao, Junling; Wang, Chenfeng (Frontiers in Chemical Engineering, 2022)
Persistence of ammonium nitrogen and heavy metals in wastewater still remains a challenge, and many wastewater treatment plants face the challenge of removing nitrogen under heavy metal stresses. There is no preferred method for the biological treatment of wastewater containing nitrogen and heavy metals with the possible exception of the anaerobic ammonium oxidation (anammox), since it has shown promise for removing nitrogen under heavy metal stresses. This article reviews the recent research results of the nitrogen-removal performance and mechanism by the anammox process under heavy metal stresses, mainly discussing the enhancing and inhibition effects of heavy metals on the performance of the Anammox reactor. The influencing mechanism of heavy metals on the microbial community and extracellular polymeric substances is also presented, and examples are given for explanation. The main problems of the present research are pointed out, and it is proposed that unifying the metal ion concentrations of inhibiting or promoting anammox activity is necessary for the development and industrial application of the anammox process. The information of this review can offer a great possibility for achieving desired nitrogen removal in wastewater treatment under heavy metal stresses and with significant energy savings.